Determinants of Innovative Teaching among the Indonesian Lecturers - M. A. Rafsanjani; E. H. Andriansyah; A. E. Prabowo; N. Laily (Moscow Polytechnic University, 2021)
Innovation is the main source to remain competitive in today's environment. As well as other employees, the lecturer is also required to do innovative teaching. But, encouraging lecturers' willingness to do innovative teaching is challenging due to the dual roles as teachers and researchers. This study explores the predictor of innovative teaching by applying the job-demands resources model as a theoretical anchor. This research used the online questionnaire to collect the data from 233 samples taken randomly  from nineteen universities in Indonesia. This study uses structural equation  modeling (SEM) to examine the research model. The result indicated that  teacher-researcher role conflict negatively predicted the innovative teaching of the lecturer. Besides, occupational well-being plays a mediating variable to explain the influence of teacher-researcher role conflict on innovative teaching. This study provides critical insight into the related stakeholders, such as the universities and related ministry, regarding the negative predictor of innovative teaching. They should discover approaches to reduce the negative effect of teacher-researcher conflict on the innovation behavior of lecturer teaching activity. The universities and  related ministries have to ease the issue regarding job role conflict.